The association of family functions in families of children who undergo organ transplantation: the quality of life of the children and their families - DÜKEN, Mehmet Emin; YAYAN, Emriye Hilal (Journal of Psychological Perspective, 2023)
Aim: Family functioning and quality of life are related. This study was to examine the association of family functioning in families of children/adolescents who had undergone organ transplantation and the quality of life of these children/adolescents and their parents. Methods: This descriptive cross-sectional study collected research data using the following tools: Child Information Form, Parent Information Form, Pediatric Quality of Life Questionnaire, Parent Quality of Life Assessment Scale, and Family Assessment Device. Results: This study found that the quality of life mean scores of children and parents were low. There was a positive relationship between the general quality of life of children who underwent organ transplantation and their psychosocial quality of life and the quality of life of their parents. This study also found a negative relationship between the psychosocial quality of life of children who had undergone organ transplantation and the subdimensions of roles, affective responsiveness, behavioral control, and general family functioning. Conclusion: This study showed that the quality of life levels of children who have undergone organ transplantation and of their parents may be low and may be associated to each other, which may lead family functioning to be negative.